2008
DOI: 10.5194/acpd-8-17939-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the relation between aerosol optical depth and PM<sub>2.5</sub> at Cabauw, the Netherlands

Abstract: Abstract. To acquire daily estimates of PM2.5 distributions based on satellite data one depends critically on an established relation between AOD and ground level PM2.5. In this study we aimed to experimentally establish the AOD-PM2.5 relationship for the Netherlands. For that purpose an experiment was set-up at the AERONET site Cabauw. The average PM2.5 concentration during this ten month study was 18 μg/m3, which confirms that the Netherlands are characterised by a high PM burden. A first inspection of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
65
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 44 publications
2
65
0
3
Order By: Relevance
“…So far, the use of spaceborne AOT for monitoring of surface PM2.5 has much been focused on the USA and China. Only few studies investigate the feasibility of monitoring particulate pollution in Europe (Kacenelenbogen et al, 2006;Pelletier et al, 2007;DiNicolantonio et al, 2009;Glantz et al, 2009;Schaap et al, 2009). Furthermore, little is known about the applicability of the AOT-to-PM2.5 relationship for rather clean conditions with a PM2.5 concentration lower than 20 mg m .…”
Section: Introductionmentioning
confidence: 99%
“…So far, the use of spaceborne AOT for monitoring of surface PM2.5 has much been focused on the USA and China. Only few studies investigate the feasibility of monitoring particulate pollution in Europe (Kacenelenbogen et al, 2006;Pelletier et al, 2007;DiNicolantonio et al, 2009;Glantz et al, 2009;Schaap et al, 2009). Furthermore, little is known about the applicability of the AOT-to-PM2.5 relationship for rather clean conditions with a PM2.5 concentration lower than 20 mg m .…”
Section: Introductionmentioning
confidence: 99%
“…Advances in satellite remote sensing have provided a cost-effective approach to frequently monitor the spatial distribution and the regional transport of aerosol particles on a large scale [8][9][10][11][12][13][14], though the discontinuous satellite observations could hardly reflect the diurnal variations of particle matters. Aerosol optical thickness (AOT), derived from satellite observations, is a dimensionless measure of aerosol abundance and atmospheric extinction of radiance over the entire air column.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2004Liu et al ( , 2005) also showed the Multi-Angle Imaging Spectroradiometer (MISR; Diner et al, 2002) on board Terra to have similar capabilities for air quality applications. Several research efforts have worked towards establishing empirical satellite-based AOD-PM relationships in different regions of the world (e.g., Engel-Cox et al, 2004;Gupta et al, 2006;Schaap et al, 2009), as well as deriving satellitebased AOD products with higher resolution for comparison to urban domains (e.g., Li et al, 2005;Kumar et al, 2007;Wong et al, 2011;Bilal et al, 2013). Meteorological parameters, such as relative humidity (RH), wind direction and speed (e.g., Gupta and Christopher, 2009a, b), are also shown to be important in establishing AOD-PM correlations.…”
Section: Introductionmentioning
confidence: 99%